2015
DOI: 10.1039/c4cp05128a
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the adsorption and reactivity of hydrogen on magnesium silicate nanoclusters

Abstract: We study nanoclusters of Mg-rich olivine and pyroxene (having (MgO)6(SiO2)3 and (MgO)4(SiO2)4 compositions) with respect to their reactivity towards hydrogen atoms, using density functional calculations. Ultrasmall silicate particles are fundamental intermediates in cosmic dust grain formation and processing, and are thought to make up a significant mass fraction of the grain population. Due to their nanoscale dimensions and high surface area to bulk ratios, they are likely to also have a disproportionately la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 31 publications
(126 reference statements)
0
32
0
Order By: Relevance
“…When compared to other siliceous models with the Mg−Si−O centers involved in the H 2 synthesis, the Fe‐POSS system favorably shifts all the energies (from thermodynamic potentials to barrierless kinetics) toward the H 2 formation because of the Fe catalytic center.…”
Section: Figurementioning
confidence: 96%
See 4 more Smart Citations
“…When compared to other siliceous models with the Mg−Si−O centers involved in the H 2 synthesis, the Fe‐POSS system favorably shifts all the energies (from thermodynamic potentials to barrierless kinetics) toward the H 2 formation because of the Fe catalytic center.…”
Section: Figurementioning
confidence: 96%
“…Though not receiving the same attention as ice and carbonaceous‐based surfaces, the theoretical analysis of siliceous surfaces like crystalline Mg 2 SiO 4 ( forsterite ), Fe 2 SiO 4 ( fayalite ), olivine and Mg‐silicates nano‐clusters has been considered . The net results showed that although H 2 formation is possible, reaction mechanisms are a function of the crystalline surfaces (001, 010, 110), atoms and defects (metal cation vacancies) where the adsorption/reaction sites are placed …”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations